MODERATE AND SEVERE LESION OF CORONARY VESSELS BY SYNTAX SCORE AS A PREDICTOR FOR IN-HOSPITAL COMPLICATIONS IN MYOCARDIAL INFARCTION AND ENDOVASCULAR TREATMENT - I. A. Urvantseva; K. Yu. Nikolaev; E. V. Milovanova; M. I. Voevoda (Российский кардиологический журнал, 2015)
Aim. To study a prognostic significance of moderate and severe lesion of coronary vessels by SYNTAX related to an occurence of in-hospital complications of ST elevation acute myocardial infarction (STEMI) after endovascular treatment.Material and methods. The severity of coronary lesion was assessed by SYNTAX in 330 consequent patients (274 men and 56 women), mean age 53,6±8,9, admitted in 4,2 hours (mediana) and in 2,1 and 7,9 hours (25th and 75th percentiles) from the onset of STEMI clinical picture. SYNTAX calculation was done afterwards by the results of coronary angiography. The assessed patients were divided into two groups: of moderate and severe coronary lesion (SYNTAX ≥23), and mild lesion (SYNTAX 0-22).Results. It was found that SYNTAX ≥23 is an independent prognostic factor for lethal outcomes (OR=10,8; 95% CI: 3,0-39,4; p<0,0001), AF (OR=3,9; 95% CI: 1,5-9,9; p=0,004) and VF (OR=3,7; 95% CI: 1,3-10,2; p=0,013), no-reflow (OR=3,6; 95% CI: 1,1-11,7; p=0,036), pulmonary edema (OR=3,0; 95% CI: 1,2-7,6; p=0,018), pleural effusion (OR=4,3; 95% CI: 1,4-13,1; p=0,010), acute left ventricle aneurisms (OR=3,9; 95% CI: 1,2-12,3; p=0,022), cardiac asthma (OR=5,8; 95% CI: 1,4-23,6; p=0,014), and heart failure Killip ≥ II (OR=2,6; 95% CI: 1,3-5,2; p=0,008).Conclusion. Moderate and svere coronary lesion by SYNTAX is an independent prognostic factor for lethal outcomes, arrhythmias, no-reflow, pulmonary edema, pleural effusion, acute left ventricle aneurisms, cardiac asthma and heart failure of Killip ≥ II during in-hospital stage of care in patients with myocardial infarction and endovascular treatment.